Rapid detection of cucumber vein yellowing virus by tissue-print hybridisation with digoxigenin-labelled cDNA probes - Rubio, Luis; Janssen, Dirk; Cuadrado, I. M.; Moreno, Pedro; Guerri, José (2017)
Hybridisation of tissue prints with nonradioactive cDNA probes was developed to detect cucumber vein yellowing virus (CVYV) in cucurbit plants. Results showed irregular distribution of the virus within cucumber, zucchini or melon plants without defined tropism for a specific tissue. Therefore, reliable diagnosis of CVYV requires analysis of tissue prints from at least five different plant sites. This detection procedure allows rapid analysis of large numbers of plants and it can be useful for epidemiological studies of CVYV and to control virus spread via eradication of early foci.